From Latin to Romance morphosyntactic typology and change - Ledgeway, Adam. (Oxford : Oxford University Press, 2012)
This volume examines grammatical changes during the transition from Latin to the Romance languages and the factors proposed to explain them. It challenges orthodoxy, presents perspectives on language change, structure, and variation, and will appeal to Romance linguists, Latinists, philologists, andhistorical linguists of all persuasions.
Series from CIP print version.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Romance languages -- Grammar, Historical; Romance languages -- Morphosyntax